High-level Operation and the Reconfiguration of Energy Policy: Geopolitical Pressure and Oil Market Stability (Case Study in Venezuela) - Joseph Robert Giri; Suspada Siswa Putra (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Geopolitical pressures on oil-producing states can reconfigure domestic political dynamics, alter the direction of energy policy, and generate spillover effects in the global oil market. Venezuela, possessing approximately 17% of global proven oil reserves, represents a critical case of a resource-rich state with high structural vulnerability to external coercive pressures. Objective: This study addresses the limitations of previous studies that tend to discuss geopolitical interventions, global power distribution, international law, and energy market dynamics separately. Methods: This study employs an explanatory qualitative approach with a single-case study design and a structured causal analysis framework. Research data were obtained from in-depth interviews with key informants, reports of international institutions, academic literature, as well as media interviews with experts, treated as supporting data. Results: The results of the study show that Venezuela is a relevant case to explain how the combination of high dependence on oil, limited deterrence capability, and external geopolitical pressures can affect the orientation of energy policy as well as increase market sensitivity to global energy supply risks. The findings of the study also indicate that although political changes in energy-producing countries do not automatically cause major global economic shocks in the short term, they can affect market expectations and energy investment prospects. Conclusion: The main contribution of this article is to offer an analytical framework that links geopolitical pressures, the vulnerability of oil-producing countries, changes in energy policy, and the dynamics of global oil markets in one integrated causal explanation.